2016
DOI: 10.1128/genomea.00936-16
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequences of Three Northern German Epidemic Staphylococcus aureus (ST247) Strains Containing Multiple Copies of IS 256

Abstract: We report the draft genome sequences of three multiresistant Staphylococcus aureus strains of sequence type 247 (ST247). The methicillin-resistant S. aureus (MRSA) SA1450/94 is vancomycin susceptible, while the clinical MRSA isolate S. aureus SA137/93A and its spontaneous laboratory mutant SA137/93G are characterized by intermediate vancomycin susceptibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Some authors reported that despite the presence of ica operon, some staphylococcal isolates produce weak biofilm production due to the inactivation of icaA by insertion of IS256 ( Cho et al, 2002 ; Kiem et al, 2004 ). Further reported that the insertion of IS256 inactivates mutS and contributes to vancomycin resistance development in vancomycin-intermediate S. aureus strains ( Kleinert et al, 2016 ). Also, the upregulation of icaA and icaD genes during acidic stress promotes biofilm formation which in-turn plays a role to resist it from acidic and alkaline environments and establishes the niche adaptation in Staphylococcus strains ( Lindsay et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors reported that despite the presence of ica operon, some staphylococcal isolates produce weak biofilm production due to the inactivation of icaA by insertion of IS256 ( Cho et al, 2002 ; Kiem et al, 2004 ). Further reported that the insertion of IS256 inactivates mutS and contributes to vancomycin resistance development in vancomycin-intermediate S. aureus strains ( Kleinert et al, 2016 ). Also, the upregulation of icaA and icaD genes during acidic stress promotes biofilm formation which in-turn plays a role to resist it from acidic and alkaline environments and establishes the niche adaptation in Staphylococcus strains ( Lindsay et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…The genomic sequences of the ST247 strains S. aureus SA1450/94, SA137/93A, and SA137/93G were determined by next-generation sequencing (NGS) using 454 sequencing technology (54). In the first de novo assembly of the NGS reads with the GS De Novo Assembler (Roche Applied Science GmbH, Mannheim, Germany), the sequences of the IS elements IS256, IS431mec, and IS1181 were recognized as repetitive sequences and were summarized as three single contigs.…”
Section: Is256 and Scv Formation In St247 S Aureus Antimicrobial Agementioning
confidence: 99%
“…Accession number(s). The sequences have been deposited in GenBank with the following accession numbers: for S. aureus SA137/93A, JWMH00000000 (JWMH01000001 to JWMH01000036); for S. aureus SA137/93G, JWMG00000000 (JWMG01000001 to JWMG01000041); and for S. aureus SA1450/94, JWMI00000000 (JWMI01000001 to JWMI01000029) (54).…”
Section: Is256 and Scv Formation In St247 S Aureus Antimicrobial Agementioning
confidence: 99%
“…Some authors reported that despite the presence of ica operon, some staphylococcal isolates produce weak biofilm production due to the inactivation of icaA by insertion of IS256 (Cho et al, 2002;Kiem et al, 2004). Further reported that the insertion of IS256 inactivates mutS and contributes to vancomycin resistance development in vancomycin-intermediate S. aureus strains (Kleinert et al, 2016). Also, the upregulation of icaA and icaD genes during acidic stress promotes biofilm formation which in-turn plays a role to resist it from acidic and alkaline environments and establishes the niche adaptation in Staphylococcus strains (Lindsay et al, 2006).…”
Section: Discussionmentioning
confidence: 99%